Meta Analysis of The Invisible Trigger: Air Pollution and Rising Asthma Cases in Adolescents - Tripathi, Shivanshi; Singh, Dhirendra; Srivastava, Rashi; Singh, Ratnesh Kumar; Tiwari, Archita; Yadav, Dr. Amrita (International Journal of Aquatic Research and Environmental Studies, 2026)
Over the past two decades, rapid urbanization, increased motor vehicle use, industrial expansion, and continued fossil-fuel combustion have maintained high levels of harmful pollutants in air such as PM2.5, nitrogen dioxide, & ozone. Although some regions have achieved improvements, global exposure remains widespread, with nearly all people living in areas that exceed WHO air-quality guidelines. These pollutants have been correlated with repressed lung development and increased asthma risk among adolescents. National data indicate that childhood and adolescent asthma prevalence increased substantially between 2005 and 2017, while studies from Delhi show prevalence rising from about 12% in the late 1990s to nearly 22% among adolescents in recent years. The increase has been linked to rapid urbanization, worsening air quality, traffic emissions, and prolonged exposure to particulate pollutants, particularly in major metropolitan cities.